IMPLEMENTASI MODEL PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN KEMAMPUAN DASAR SISWA SEKOLAH DASAR - Hesti, - (2007)
ABSTRACT The Implementation of Thematic Model of Instruction to imorov* Student's Basic Competencies Bv :. Hestv NIM : 057122 The study aimed at implementing thematic instruction model that could be able to correct and increase the quality of instruction and could be able to increase the basic ability ofelementary school students. The study conducted by using action classroom research in three elementary schools, which were the following categories, high, average and low. The subjects of the study were teachers and students at the second grade of elementary schools. Based on the result of five cycles known that the teachers in those schools had ability in implementing the thematic instruction . The ability of those teachers increased when the action test done. The activities of student learning, namely their abilities of questioning, giving the opinion and collaborating in those three schools also increased in line with the increasing of teachers ability in implementing the thematic instruction model. The ability of students to master learning materials increased this proves that the implementation of thematic instruction model would not only correct and increase learning process in the class, but also it would increase students master material instruction. The result were different. Those differences influenced by many factors, such as teachers quality, students character, the availability of facilities and environmental factor like headmaster leadership. This study gave as generic model thematic instruction model, meaning that thematic instruction model enables to be implemented on other schools that minimallv have the same characteristics as the low schools.